2005
DOI: 10.1080/00288330.2005.9517381
|View full text |Cite
|
Sign up to set email alerts
|

Size trends and population characteristics of striped marlin,Tetrapturus audaxcaught in the New Zealand recreational fishery

Abstract: Size trends and population characteristics of striped marlin, Tetrapturus audax, caught in the New Zealand recreational fishery were evaluated using club records from the Bay of Islands Swordfish Club (BOISC) from 1925 to 2003 (n = 15 114) and biological samples from northern New Zealand collected from 1985 to 1994 (n = 684). Average weight (kg) ± SE of striped marlin declined 6-9 kg every 20 years between 1925 (124.2 ± 1.0 kg) and 2003 (100.1 kg ± 0.4). Weight (H 14843 = 444.58, P < 0.001) and condition (H 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 15 publications
0
29
0
2
Order By: Relevance
“…Most age estimates conducted on billfishes have not been validated in any form (Skillman and Yong 1976;Hedgepeth and Jolley 1983;Davie and Hall 1990;Melo-Barrera et al 2003;Kopf et al 2005;Hoolihan 2006). In the absence of an absolute form of age validation, the periodicity of annulus formation and location of the first annulus should be identified (Campana 2001).…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most age estimates conducted on billfishes have not been validated in any form (Skillman and Yong 1976;Hedgepeth and Jolley 1983;Davie and Hall 1990;Melo-Barrera et al 2003;Kopf et al 2005;Hoolihan 2006). In the absence of an absolute form of age validation, the periodicity of annulus formation and location of the first annulus should be identified (Campana 2001).…”
Section: Validationmentioning
confidence: 99%
“…Growth models have been developed for several species including swordfish (Ehrhardt 1992;Tserpes and Tsimenides 1995;Sun et al 2002;DeMartini et al 2007), sailfish, Istiophorus platypterus (Hedgepeth and Jolley 1983;Chiang et al 2004;Hoolihan 2006), black marlin, Makaira indica (Speare 2003), and striped marlin (Skillman and Yong 1976; Melo- Barrera et al 2003;Kopf et al 2005). Age estimates have also been made on blue marlin, Makaira nigricans (Hill et al 1989;Wilson et al 1991) but growth models have been restricted to juveniles due to the difficulties of ageing older fish.…”
Section: Introductionmentioning
confidence: 99%
“…For the marlins M. nigricans and T. albidus distributed off the coast of Venezuela, Marcano et al (2001) documented changes without significant variations. In the case of the striped marlin (Tetrapturus audax) caught in the New Zealand recreational fishery from 1925 to 2003, Kopf et al (2005) observed that the mean weight of this species declined progressively from 6 to 9 kg over every 20 years; however, in 2003 they oberved an unusual presence of adult organisms, which significantly increased the mean size in the catches. Nonetheless, these fluctuations were not considered relevant as the mean size did not fall below the length at first maturity (Baum andMyers 2004, Kopf et al 2005).…”
Section: Estructura De Tallasmentioning
confidence: 96%
“…Para las especies M. nigricans y T. albidus que se distribuyen frente a las costas de Venezuela, Marcano et al (2001) documentaron cambios sin variaciones significativas. En el caso del marlín rayado (Tetrapturus audax) capturado por la flota deportiva de Nueva Zelanda de 1925 a 2003, Kopf et al (2005) documentó que el peso promedio de esta especie declinó progresivamente de 6 a 9 kg por cada 20 años; no obstante, en 2003 estos autores observaron una inusual presencia de organismos adultos, incrementando significativamente la talla promedio de las capturas. Sin embargo, estas fluctuaciones no se consideraron relevantes dado que la talla promedio no decayó por debajo de la longitud de primera madurez (Baum y Myers 2004, Kopf et al 2005.…”
Section: Estructura De Tallasunclassified
See 1 more Smart Citation